PERAN INSPEKTORAT KABUPATEN/KOTA SEBAGAI LEMBAGA PENGAWASAN INTERNAL PEMERINTAH DAERAH MENUJU TATA KEPEMERINTAHAN DAERAH YANG BAIK - Achmad Fauzi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
Supervision is essentially an act of judging or testing whether something has been going according to a predetermined plan. With the supervision will be found that mistakes will eventually attempted repairs, the most important not to mistake happen again. Supervision is always required for all actions the central government and local authorities. Its main purpose is to avoid actions that harm the public interest, or at least to reduce as much as possible it happened. Supervision is more focused or focused on the evaluation and corrective actions to the results that have been achieved, with the intention that the proceeds according to plan. Therefore, the role of oversight agencies, in particular local government agency internal controls (Inspectorate) in the county / city in the course of carrying out the task of supervision of the machinery of government in the area of governance in order to realize good local governance, is crucial. Because the performance capabilities of internal oversight agencies also contribute to determine the successful management of local governance, since this institution has a range of supervisory duties are quite broad and has a strong position and strategic. This is because the Regional Inspectorate districts / cities in its duty to supervise not only the aspects of the use of financial / budget area, but his supervision more broadly is regarding the duties and functions, performance, and discipline region official. To realize this, the role of internal oversight agencies (Inspectorate) district / city, should be improved and optimized, so that local governance that can both manifestation.